Medieval Theoretical Principles of Medicine in Ibn Sīnā’s al-Qānūn fī al-Ṭibb and al-Dhahabī’s al-Ṭibb al-Nabawī - Muhammad Fawwaz Muhammad Yusoff; Nur Izah Ab Razak (University of Malaya, 2024)
Indexed by WOS/MYCITE